The relationship between cardiorespiratory fitness and indices of fat mass and fat-free mass in adults - Popp, Collin J.; Jesch, Elliot D. (Frontiers in Sports and Active Living, 2025)
PurposeCardiorespiratory fitness (CRF) independently predicts cardiovascular disease risk and mortality. In addition, body composition levels characterized by excess adiposity (fat mass) and low levels of fat-free mass (FFM) are strongly associated with poor health status. The relationship between CRF and body composition, especially indices adjusted for height [fat mass index (FMI), fat-free mass index (FFMI)] has not been well established in otherwise healthy adults.MethodsA sample (n = 82) of adults completed measures for body composition using dual-energy x-ray absorptiometry and estimated V˙O2max by way of an Åstrand-Rhyming submaximal cycle ergometer test. Total daily energy expenditure (TDEE) and moderate-to-vigorous physical activity (MVPA) were measured using a SenseWear Armband activity monitor. The associations between body composition (FMI, FFMI), and CRF were examined using multiple linear regression models adjusting for sex (model 1) and TDEE (model 2).ResultsParticipants were young (age: 24 ± 9 year), 64% female, with a BMI of 25.4 ± 4.9 kg·m−2. The mean absolute and relative estimated V̇O2max were 3.02 ± 1.0 L·min−1 and 42.1 ± 12.2 ml·kg−1·min−1, respectively. FMI was negatively associated CRF (L·min−1) in model 2 (B = −0.106, 95%CI −0.16, −0.05, p < 0.001) but not model 1 (B = −0.011, 95%CI −0.03, 0.01, p = 0.271). FFMI was positively associated with CRF (L·min−1) (model 1: B = 0.087, 95%CI 0.03, 0.14), p = 0.004) but not after adjusting for TDEE (model 2: B = 0.026, 95%CI −0.07, 0.12, p = 0.585).ConclusionFM adjusted for height (FMI), but not fat-free mass (FFMI), is negatively associated with cardiorespiratory fitness in adults.